Use of Media in Hijaiyyah Letter Recognition in Early Childhood - Zara, Mutiara; Wulan, Sri; Sarifah , Iva (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Al-Qur'an Education Park is able to provide basic skills for learning and understanding the Al- Qur'an. The introduction of the Qur'an to children can already be done when the child is still in the womb. But formally, the introduction of the Qur'an is carried out when the child is 4 years old. When children enter early childhood education school, children begin to be taught the introduction of hijaiyyah letters. The introduction of hijaiyyah letters for early childhood requires the right strategy. So that the goal of introducing hijaiyyah letters to children is achieved. Media are all kinds of components or materials that exist in the student environment that can stimulate students to learn. The purpose of this study is to determine the role of media and what media are used by teachers in introducing hijaiyyah letters to early childhood. This research uses literature study techniques. The results showed that the media that can be used by teachers in the introduction of hijaiyyah letters and have proven to be able to improve children's ability to recognize hijaiyyah letters include dice, letter cards, flannel boards, Arabic Alphabet for Kids, and educational game applications. The literature study shows that the media has an important role in the introduction of hijaiyyah letters in early childhood, including: the media gives an impression and pays attention to the learning process; learning activities become active and fun; the message conveyed by the teacher becomes conveyed; learning is more effective and not monotonous; and it provides convenience and knowledge of new information received by children